Social Skills Training and Its Contribution to the Realization of Child-Friendly Schools: An Analysis of the Impact of Group Guidance - Nailah Rizqia Azhar; Sunawan Sunawan (Universitas Negeri Semarang, 2025)
Child-Friendly Schools are a strategic approach to creating a safe, inclusive, and violence-free learning environment. One of its main foundations is students' social skills that support positive individual interactions. However, these skills do not develop evenly and are influenced by various personal and social factors. This study explores students' experiences after participating in social skills group counseling and its contribution to the realization of Child-Friendly Schools. This study employs a qualitative phenomenological approach, collecting data from 16 junior high school students who have participated in group counseling sessions through observation, worksheets, field notes, and reflections. Analysis was conducted using van Manen's thematic approach. The findings reveal four main themes: awareness of positive communication, reflection on the implementation process of group counseling, growth in empathy and social perspective, and the application of social skills at school. The findings indicate that group counseling creates a safe reflective space, promotes behavioral change, and fosters values of empathy, tolerance, and appreciation for diversity. This study provides an in-depth understanding of students' social-emotional transformation through structured group dynamics with a humanistic approach.